Let $G$ be a $p$-group, $\{e\}\not= H\subseteq G$ be a subgroup of $G$ such that $G' = H'$. Is it true that $c(G) = c(H)$, where $c(\cdot)$ denotes the nilpotency class of a group?

  • 2
    $\begingroup$ I suppose you assume $H$ to be non-trivial, otherwise $G = C_p$ for $p$ prime works as a counterexample. $\endgroup$ Sep 20, 2023 at 8:07
  • 1
    $\begingroup$ Clearly $c(H)=1$ implies $c(G)=1$. Actually, it is also true that $c(H)=2$ implies $c(G)=2$. This is a consequence of the Hall-Witt identity $[[a,b^{-1}],c]^b \cdot [[b,c^{-1}],a]^c \cdot [[c,a^{-1}],b]^a = 1$, rewritten in the form $[[h_1,h_2],g]^{h_2^{-1}} \cdot [[h_2^{-1},g^{-1}],h_1]^c \cdot [[g,h_1^{-1}],h_2^{-1}]^{h_1} = 1$. If $H$ is 2-step nilpotent and $H'=G'$, both $[h_2^{-1},g^{-1}]$ and $[g,h_1^{-1}]$ are in $H'$ and hence both right-hand double brackets are trivial, so eventually $G$ centralizes $H'=G'$. $\endgroup$
    – YCor
    Sep 20, 2023 at 8:33
  • 1
    $\begingroup$ Finally this argument can be adapted to the general case, so I wrote an answer. $\endgroup$
    – YCor
    Sep 20, 2023 at 9:01

1 Answer 1


This is true in an arbitrary nilpotent group.

Namely, for a nilpotent group $G$ and subgroup $H$ with $G'=H'$, let us check that $G^{(i)}=H^{(i)}$ for all $i\ge 2$ (lower central series. In particular, they have the same class (with the exception of $c(G)=1$, $c(H)=0$, i.e. $G$ nontrivial abelian $H$ trivial).

The case $i=2$ is the assumption $G'=H'$.

We use in general the Hall-Witt identity. $$[[a,b^{-1}],c]^b \cdot [[b,c^{-1}],a]^c \cdot [[c,a^{-1}],b]^a = 1$$ (with conventions $x^y=y^{-1}xy$ and $[x,y]=x^{-1}y^{-1}xy$).

Suppose that $G^{(j)}=H^{(j)}$ for all $2\le j\le i$. For $g\in G$, $h\in H$ and $s\in H^{(i-1)}$, this formula shows that $[[h,s],g]$ belongs to $$[[G,H],H^{(i-1)}][[H^{(i-1)},G],H].$$ We have $$[[H^{(i-1)},G],H]=[[G^{(i-1)},G],H]=[G^{(i)},H]=[H^{(i)},H]=H^{(i+1)}.$$ Also $[[G,H],H^{(i-1)}]=[[H,H],H^{(i-1)}]$ is contained, again using the Hall-Witt identity, in $[[H^{(i-1)},H],H]=H^{(i+1)}$. Hence $[[h,s],g]\in H^{(i+1)}$. Since such elements $[h,s]$ generate $H^{(i)}=G^{(i)}$, we deduce that $$G^{(i+1)}=[G,G^{(i)}]\subseteq [H,H^{(i)}]=H^{(i+1)}.$$

(By the way, this argument also works in the context of Lie rings.)

  • $\begingroup$ Thank you! mathoverflow.net/questions/454950/… is another question. $\endgroup$
    – solver6
    Sep 20, 2023 at 10:03
  • 1
    $\begingroup$ You could also phrase your proof in terms of the three subgroups lemma (which follows from the Hall-Witt identity): Let $N$ be a normal subgroup of $G$ and $A,B,C \leq G$. If two among the subgroups $[A,B,C]$, $[B,C,A]$, $[C,A,B]$ are contained in $N$, then all of them are. ${}{}$ By the way, the problem appears in exercise 2.10 in Chap 4 of Suzuki, Group Theory II. Also in Corollary 1 of "Some sufficient conditions for a group to be nilpotent, P. Hall, Illinois J. Math. 2(4B): 787-801 (December 1958). DOI: 10.1215/ijm/1255448649". $\endgroup$ Sep 20, 2023 at 10:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.